2021
DOI: 10.1016/j.jhepr.2021.100331
|View full text |Cite
|
Sign up to set email alerts
|

International study on the outcome of locoregional therapy for liver transplant in hepatocellular carcinoma beyond Milan criteria

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…[1][2][3] Even though a great progress has been made in the treatment of HCC including curative resection or liver transplantation, tumor-directed therapies such as radiofrequency ablation, transarterial chemoembolization (TACE), radioembolization, as well as new systemic therapy beyond sorafenib, disease prognosis remains very poor. [4][5][6] Recent HCC surveillance data from the United States show improved 5-year overall survival following treatment in HCC diagnosed in its early stages (44% versus 11%). [7][8][9][10][11] Liver ultrasound (US) alone or combination with serum alpha-fetoprotein (AFP) every 6-months is the standard of care for HCC screening of patients with cirrhosis, although this approach lacks the sensitivity and specificity to reliably detect HCC at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Even though a great progress has been made in the treatment of HCC including curative resection or liver transplantation, tumor-directed therapies such as radiofrequency ablation, transarterial chemoembolization (TACE), radioembolization, as well as new systemic therapy beyond sorafenib, disease prognosis remains very poor. [4][5][6] Recent HCC surveillance data from the United States show improved 5-year overall survival following treatment in HCC diagnosed in its early stages (44% versus 11%). [7][8][9][10][11] Liver ultrasound (US) alone or combination with serum alpha-fetoprotein (AFP) every 6-months is the standard of care for HCC screening of patients with cirrhosis, although this approach lacks the sensitivity and specificity to reliably detect HCC at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective multicenter study by Mehta et al, which followed 109 patients who were eventually transplanted after DS, found 1- and 5-year survival rates of 95% and 80%, respectively 17 . Degroote et al retrospectively investigated patients from 47 different centers who received bridging or DS LRT before liver transplant and showed that patients after DS had similar posttransplant outcomes compared to those within Milan criteria 5 . These findings were corroborated by a systematic review and meta-analysis by Tan et al, which demonstrated a high success rate of DS, with greater than 50% of patients eventually receiving transplants, and a 74% 5-year survival based on intention-to-treat analysis 18 …”
Section: Discussionmentioning
confidence: 99%
“…The response to DS therapy can also serve as a predictor for posttransplant prognosis. Patients within UCSF criteria at listing and successfully downstaged have similar posttransplant outcomes compared with those within Milan at listing 5 . National and international guidelines have now recommended locoregional therapy to downstage patients to be within the Milan criteria and allow more patients with HCC to be eligible for transplant listing 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…The UCSF criteria might be considered a reasonable upper limit for applying downstaging protocols on a solely morphometric basis. However, in the all-comers cohort, a proportion of patients can be cured by LT, although the likelihood is clearly lower ( 20 , 21 ). Considering this, it might be ‘too restrictive’ or more precisely ‘too unspecific’, if patient selection for downstaging is only based on tumor size and number.…”
Section: Still Not Outdated: Morphometric Parameters—should There Be ...mentioning
confidence: 94%